Subsurface upgrading of heavy crude oils and bitumen - Ovalles, César (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
Heavy crude oils and bitumen represent more than 50% of all hydrocarbons available on the planet. These feedstocks have a low amount of distillable material and high level of contaminants that make their production, transportation, and refining difficult and costly by conventional technologies. Subsurface Upgrading of Heavy Crude Oils and Bitumen is of interest to the petroleum industry mainly because of the advantages compared to aboveground counterparts. The author presents an in-depth account and a critical review of the progress of industry and academia in underground or In-Situ upgrading of heavy, extra-heavy oils and bitumen, as reported in the patent and open literature. This work is aimed to be a standalone monograph, so three chapters are dedicated to the composition of petroleum and fundamentals of crude oil production and refining. Key Features: Offers a multidisciplinary scope that will appeal to chemists, geologists, biologists, chemical engineers, and petroleum engineers Presents the advantages and disadvantages of the technologies considered Discusses economic and environmental considerations for all the routes evaluated and offers perspectives from experts in the field working with highlighted technologies
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Chemistry / Industrial & Technical; Petroleum -- Refining; Petroleum -- Analysis; Bitumen